Reconstruction the Major’s Policy in Order to Economic and Poverty Recovery in Pandemic at Pasuruan City East Java, Indonesia - Ana Fauzia (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
The Covid-19 pandemic not only has an impact on the health aspect of the community, but also has an impact on the declining level of the economy and community welfare. Based on data from the Central Statistics Agency (BPS) of Pasuruan City, since the arrival of the Covid-19 pandemic, poverty in Pasuruan City has increased by 0.20 percentage points. The purpose of this study is to analyze how the impact of the Covid-19 pandemic on the economy of the community in Pasuruan City, as well as solutions or policies that can be implemented by the Pasuruan City Government. The method used in this research is normative legal research using the approach of applying the law, conceptual, and case. The results of the study show that the Covid-19 pandemic has had a tremendous impact on various sectors, one of which is the economy of the people of Pasuruan City. So that the situation and conditions need responsive efforts from the Regional Government of Pasuruan City in where the steps from the demand side themselves, could be in the form of (1) tax incentives, loan interest subsidies, and credit restructuring to the firms (including micro, small, and medium enterprises) to jumpstart their activities; (2) employment and income provision for the furloughed (unpaid leave) workers to make sure that the workers have a decent livelihood and to prevent them from falling into poverty; and (3) inclusive protection for the workers, both in terms of social protection and employment agreement. As for the supply side, efforts can be made by (1) increasing access to secondary and tertiary education; (2) enhance the quality of education; and (3) provide training and education for workers and everyone over the lifecycle. So that through this idea it is hoped that it can be a solution for the economic recovery of the community in Pasuruan City due to the Covid-19 Pandemic.